Macroeconomic Variables and Stock Market Performance in Sri Lanka: An ARDL Bound Testing Approach - Kengatharan, L.; Jeyan Suganya, D.F. (South Asian Journal of Business Insights, 2021)
The aim of the study is to examine the impact of macroeconomic variables on stock market performance in Sri Lanka. This study uses yearly data collected from the annual report of the Central Bank of Sri Lanka for the period from 1990 to 2019. Macroeconomic variables used in this study are interest rate, inflation rate, real exchange rate, and money supply while All Share Price Index (ASPI) is used to measure the stock market performance. Inflation rate and interest rate are found stationary at zero levels while exchange rate, money supply and stock market performance are found stationary at levels one in the Augmented Dickey-Fuller (ADF) test. No serial correlation is found among variables by employing Breusch-Godfrey LM Test. The Auto-Regressive Distributed Lag (ARDL) bounds test is used to test the long-run and short-run relationships between variables. The empirical result reveals that there is a negative and significant impact of interest rate and inflation rate on stock market performance while exchange rate and money supply do not hold any significant impact on stock market performance in the long-run. Further, it is found that there is a negative and significant impact of interest rate on stock market performance in the short run.
Keywords: ARDL Bound Test; ASPI; Macroeconomic Variables; Stock Market Performance